A new, critically endangered species of Aiphanes (Arecaceae) from Colombia - Bernal, Rodrigo; Hoyos-Gómez, Saúl E.; Borchsenius, Finn (Phytotaxa, 2017)
Aiphanes argos is a new species of palm segregated from Aiphanes parvifolia, which is now recognized to be a species complex. Aiphanes argos is one of the few rheophytic members of the palm family, and is endemic to a small area in the Samaná Norte River canyon in Antioquia, Colombia, where it is critically endangered because its populations are threatened by the damming of the river for a hydroelectric plant. The epiteth argos is the name of the conglomerate that intends to build the dam, and is given to the palm as a plea for the conservation of the Samaná Norte River canyon.